THE CRISIS OF ECONOMICS AND FOR SEARCH OF THE NEW PARADIGM (Globalization and Business, 2018)
The article analyzes the crisis in the economics, its primary causes and its manifestations. It shows how tra- ditional economics “turns a blind eye” to many signifi- cant aspects of economic reality. Within this crisis, the economy lags behind the economic reality and so vari- ous economic theories are used to attempt to interpret the economic phenomena.  Some of the clearest exam- ples of economies falling outside of reality are seen in the transition economies of the post-Communist period on their way to a market economy as well as the events of the global financial and economic crisis in 2007-2009. The most recent example of the crisis in economics is cryptocurrency which has already spread over almost the entire world over the past several years but which has not yet become a topic of systematic study in eco- nomics.In order to overcome the crisis situation in eco- nomics, it will be of utmost importance as to how well the human factor is reflected in economic studies and to what extent it will be approximated to the behaviorthat is characteristic of human beings in reality. For this purpose, economists must apply the knowledge about human nature that has been amassed in the field of so- cial sciences such as philosophy, psychology, law and po- litical science.For the development of economics and for its rel- evant transformation, the conditions referred to in the traditionally used phrase “other things equal” (“ceritas- paribas”) need to be minimized in economic studies. This will be possible if an economic study relies not only (and in certain cases not to a greater extent) on mathe- matics but also on philosophy, psychology, law, history, geography and political science. In this regard, econo- mists need to conduct studies by expanding their scope; that is, along the lines set out by the above-mentioned fields of the social sciences.Given the variety of economic theories, seeking possible ways to synthesize them becomes of great im- portance and this will assist economists in perceiving a given economic reality in a comprehensive way.